2021
DOI: 10.1111/jocn.15826
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and implementation of evidence‐based practice among nurses in the nursing homes of a Swiss canton: An observational cross‐sectional study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Studies utilizing the ARCC model indicate that there is a strong positive relationship between the beliefs held by practitioners and implementation in clinical practice [22]. Similar studies, using the same scales also found a positive correlation between beliefs and implementation, which indicates that the stronger nurses' beliefs are about the benefits of EBP, the higher their implementation rate in clinical practice [23]. Time throughout the literature was identified as the most salient factor impacting negatively on nurses' ability to implement EBP in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Studies utilizing the ARCC model indicate that there is a strong positive relationship between the beliefs held by practitioners and implementation in clinical practice [22]. Similar studies, using the same scales also found a positive correlation between beliefs and implementation, which indicates that the stronger nurses' beliefs are about the benefits of EBP, the higher their implementation rate in clinical practice [23]. Time throughout the literature was identified as the most salient factor impacting negatively on nurses' ability to implement EBP in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…We also know that practical nurses rarely access current research evidence in their workplaces to guide their practice (Phillips & Neumeier, 2018). This emphasizes the need for targeted and tailored support and further EBN training in these settings, in particular (Perruchoud et al., 2021; Phillips & Neumeier, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Individual skills (Perruchoud et al., 2021; Yoder et al., 2022; Yoo et al., 2019) and attitudes or beliefs in the value of EBN are linked to how EBN is perceived and implemented (Alqahtani et al., 2020; Cleary‐Holdforth et al., 2021; Stokke et al., 2014; Yoo et al., 2019). Nurses have positive attitudes toward EBN (Alanen et al., 2009; Stokke et al., 2014), and they believe in its value, but they need more knowledge and skills to implement it (Alqahtani et al., 2020; Cleary‐Holdforth et al., 2021; Perruchoud et al., 2021; Yoder et al., 2022). In addition, organizational culture and the supporting structures of the organization are associated with the implementation of EBN (Clarke et al., 2021; Cleary‐Holdforth et al., 2021; Yoder et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, studies investigating the attitudes towards EBP and recording its level of implementation have been conducted among nurses and allied health care providers [ 41 48 ]. The results are comparable to the studies cited above, with generally positive attitudes towards EBP but unsatisfactory implementation into clinical practice [ 43 , 46 ].…”
Section: Introductionmentioning
confidence: 99%